Improving Equitable Access to Imaging: Developing an On-Site Ultrasound Service at a Student-Run Free Clinic - Neel, Nicholas; McMillan, Aislinn; Hsieh, Lee; Bazzy, Jimmy; Tadros, Anthony; Tamayo-Murillo, Dorathy (Journal of Student-Run Clinics, 2022)
Background: Student-run free clinics (SRFC) provide comprehensive primary care for uninsured populations throughout the country. However, imaging remains a barrier to care for underserved communities that experience inequitable access to healthcare. In this study, we describe the establishment of a radiology specialty clinic (RSC) that served as an in-house ultrasound imaging service at our institution’s SRFC. Methods: Between September 2019 and March 2020, patients were scheduled for imaging at the free clinic site, and studies were performed and read by institutional radiologists. Patient data were reviewed to assess patient demographics, study indication, ultrasound type, and time between referral and appointment. Lastly, imaging utilization was examined seven months prior to and seven months after implementing the free ultrasound clinic to assess any changes in usage, wait time, or referral patterns using Fischer’s exact test and unpaired student t-tests. Results: A total of 10 patients were seen during the clinic’s operation, with 11 studies being performed. Overall, usage patterns stayed consistent pre and post-implementation. There was no significant difference in wait times between referral and appointment (pre-RSC 15 days vs. post-RSC 18.5 days, p=0.91) and the RSC demonstrated a total cost savings of 770 to the clinic. Conclusions: We describe the implementation of an in-house ultrasound imaging service at our SRFC. The RSC provided increased access to imaging, demonstrated cost-savings to the SRFC, and had no negative effects on ultrasound usage or wait times between referrals and appointments.